HnRNPK knockdown alleviates NLRP3 inflammasome priming by repressing FLIP expression in Raw264.7 macrophages. (1st January 2020) - Feng, Junxia; Li, Hongyan; Li, Jingchun; Meng, Ping; Wang, Lina; Liu, Chunli; Zhao, Shili; Sun, Wei; Zhang, Yunfang
ABSTRACT: Objectives: Inflammation is an important predisposing and progressive factor in chronic kidney disease (CKD). Heterogeneous nuclear ribonucleoprotein K (hnRNPK) is associated with many fundamental cellular processes, but in chronic inflammatory pathologies remains unclear. Methods: An in vitro peripheral inflammation model was established using lipopolysaccharide (LPS)-stimulated mouse RAW264.7 macrophages, followed by inflammasome activation by ATP treatment. Knockdown of hnRNPK by sihnRNPK and FLICE-like inhibitory protein (FLIP) by siFLIP transfection were achieved in Raw264.7 macrophages. ELISA was used to determine the expression of IL-1β, IL-18 and TNF-α. Real time PCR was applied to detect the mRNA levels of hnRNPK, NOD-like receptors family pyrin domain-containing 3 (NLRP3), FLIP, Caspase-1, IL-1β and IL-18. Western blot and immunofluorescence were performed to detect relevant protein expressions. Co-immunoprecipitation (Co-IP) was used to assess the interaction of hnRNPK with FLIP. Results: Results showed that LPS plus ATP activated NLRP3 inflammasome, which evidenced by the up-regulation of TNF-α, IL-1β and IL-18. Notably, hnRNPK and FLIP were significantly up-regulated in activated NLRP3 inflammasome of macrophages. HnRNPK or FLIP knockdown significantly suppressed the activation of NLRP3 inflammasome, as reflected by down-regulation of Caspase-1, IL-1β and IL-18. Importantly, hnRNPK could directly bind to FLIP in activated NLRP3 inflammasome. Discussion: Our findings suggest that hnRNPK could promote the activation of NLRP3 inflammasome by directly binding FLIP, which might provide potential new therapeutic targets for CKD. GRAPHICAL ABSTRACT: